Circuit systems with MATLAB and PSpice - Yang, Won Y. (John Wiley & Sons, 2007)
Software tools applied to circuit analysis and design are rapidly evolving, enabling students to move beyond the time-consuming, math-intensive methods of traditional circuit instruction. By incorporating MATLAB 7.0 and PSpice 10.0, alongside systematic use of the Laplace transform, Yang and Lee help readers rapidly gain an intuitive understanding of circuit concepts. Unified scheme using the Laplace transform accelerates comprehension Focuses on interpreting solutions and evaluating design results, not laborious computation Most examples illustrated with MATLAB analyses and PSpice simulations Downloadable programs available for hands-on practice Over 130 problems to reinforce and extend conceptual understanding Includes expanded coverage of key areas such as: Positive feedback OP Amp circuits Nonlinear resistor circuit analysis Real world 555 timer circuit examples Power factor correction programs Three-phase AC power system analysis Two-port parameter conversion Based on decades of teaching electrical engineering students, Yang and Lee have written this text for a full course in circuit theory or circuit analysis. Researchers and engineers without extensive electrical engineering backgrounds will also find this book a helpful introduction to circuit systems.